Partial upper sternotomy for aortic valve replacement provides similar mid-term outcomes as the full sternotomy - Hlavicka, Jan; Janda, David; Budera, Petr; Tousek, Petr; Maly, Marek; Fojt, Richard; Linkova, Hana; Holubec, Tomas; Kacer, Petr (Journal of thoracic disease, 2022)
Background: Minimally invasive aortic valve replacement via upper partial sternotomy (MiniAVR) provides very good short-term results and delivers certain advantages in the postoperative course. There is limited data regarding the mid-term mortality and morbidity following this minimally invasive surgery. Methods: We provide a retrospective analysis of the patients, undergoing MiniAVR versus full sternotomy (FS) for aortic valve replacement with biological prosthesis. As the primary combined end-point the combination of death, stroke, and rehospitalization within 3 years postoperatively was defined. Data have been collected from National Cardiac Surgery Registry and insurance companies. Results: Two hundred consecutive patients with aortic valve replacement (100 ministernotomy in MiniAVR group and 100 full sternotomy in FS group) with biological prosthesis were included in this study. Ministernotomy had longer cross-clamp and bypass times (median difference 6.5 min, P=0.005, and 8.5 min, P=0.002 respectively). Patients operated via upper partial sternotomy had a lower postoperative bleeding [300 mL (IQR, 290) vs. 365 mL (IQR, 207), P=0.031]. There was no difference in the 3-year mortality (14% vs. 11%, P=0.485). The mean number of readmission 3 years after surgery per capita was almost the same in both groups (1.65 vs. 1.60, P=0.836). Median time to the first readmission was longer in the MiniAVR group (difference 8.9 months). The incidence of combined end-point during 3 years postoperatively in both groups was not statistically different (P=0.148), as well as readmissions from cardio-vascular reasons (subhazard ratio 0.90, P=0.693). Conclusions: Upper partial sternotomy can be performed safely for aortic valve replacement, without increased risk of death, stroke or re-admission in 3 years postoperatively.